Brugada syndrome—the missed epidemic. Issue 6 (1st November 2000) - Butler, J M
Abstract : About 10–20% of patients dying suddenly or resuscitated from ventricular fibrillation do not have demonstrable heart disease. These people are often young and tragically in some cases sudden death is the first and only clinical event. One of the three main electrophysiological diagnoses to be considered in these situations is the Brugada syndrome. A case of Brugada syndrome is described, together with an example of the classic electrocardiographic manifestations and a discussion of the possible aetiology, diagnosis and management of this condition.